Evolution of the Brightest Cluster Galaxies - Zhao, Dongyao (2016)
In this thesis, I explore the evolution of the brightest cluster galaxies (BCGs) over the last 10 billion years through detailed studies of both local BCGs from SDSS and their high-z progenitors from CANDELS UDS.